Total hip arthroplasty and perioperative management of a patient with hip osteonecrosis secondary to hypopituitarism due to Sheehan syndrome: a case report and literature review - Ma, Biao; Li, Jun; Ma, Tao; Shang, He; Liu, Xueqi; Yang, Tianxiang; Liang, Jinpeng; Ma, Yaxing; Wang, Ruoyu; Ma, Hui; Liu, Jiao; Chen, Desheng (Frontiers in Surgery, 2026)
BackgroundSheehan's syndrome, a rare disorder resulting from postpartum hemorrhage-induced necrosis of the anterior pituitary gland, necessitates long-term hormone replacement therapy with glucocorticoids. This predisposes patients to severe complications, including rapid-progression osteonecrosis of the femoral head (ONFH), which carries a high disability rate.MethodsWe report a 63-year-old female with Sheehan's syndrome diagnosed 30 years ago, managed with sustained prednisone and levothyroxine. She presented with 10 years of bilateral hip pain and imaging-confirmed bilateral ONFH at ARCO stage IV. A multidisciplinary team (MDT) approach was implemented: endocrinology optimized preoperative hormone regimens, orthopedics planned total hip arthroplasty (THA) based on bone density assessments, and anesthesiology confirmed tolerability for intraspinal anesthesia. After stabilizing physiological parameters, left THA was performed.ResultsIntraoperative hydrocortisone infusion maintained hormonal homeostasis. The surgery proceeded uneventfully; however, an allergic reaction occurred during blood transfusion, which was promptly controlled. Postoperative MDT-coordinated care enabled ambulation with a walker within one week, with unrestricted left hip mobility and no complications (e.g., infection, prosthesis loosening).ConclusionTHA for glucocorticoid-induced ONFH in Sheehan's syndrome entails challenges such as perioperative hormonal instability, elevated infection risk, and impaired bone healing. The MDT approach ensures comprehensive risk mitigation, facilitating surgical success and patient safety. Long-term follow-up for hormone levels, bone density, and prosthesis status is warranted.